The Alignment of Standards and 21st Century Literacy. - Villanueva, Alison; Fox, Elizabeth (International Journal of the Humanities, 2011)
At the beginning of the 1990's the United States made a move towards a standards-based education driven by the perception that the American education system was losing ground internationally, and that it must be drastically reformed in order to provide a competitive 21st century workforce. After twenty years however, a "standards-based accountability system" has been replaced with a "test based accountability system " that is far from representing the common standards (Forgione & Doorey, 2010). After years of implementing standardized tests, it is clear that these tests assess student knowledge and understanding at basic levels and rarely give a full picture of what a student can academically do. State and national policy makers, educators, industry and business leaders agree that because of globalization, the American workforce must become better prepared to compete internationally. Most also agree that there needs to be a sea change in the American educational system to adequately prepare the American labor force (Tough, 4). The need and opportunity for such a change is at hand. Legislation on both the national and state levels, motivated by "Race to the Top" is reshaping education, challenging unions (New York Times, 1) and revisiting both standards and assessment. We recommend a new work group, comprised of representatives from a broad range of stakeholders who do not have direct economic ties to the current standards and assessment industry. This new workgroup would be charged with developing common standards and assessments that are firmly based in a critical/multi-literacy definition of reading, and are more likely to create the changes in instruction that will prepare our young people to succeed in college and in the workplace.